The polyamorous Christ: on the sexual ethics of incarnation - Congdon, David W. (Theology & sexuality, 2025)
This article aims to initiate ‘polyamorous theology’ as a field of study. Toward this end, it begins by addressing some of the principal objections, both general and theological, to polyamory, pointing out how theologically thin even the supposedly ‘theological’ objections are. In an effort to find a positive basis for polyamory in Christian theology, some have turned to the doctrine of the trinity, understanding the godhead as a divine ‘throuple.’ This view depends on a social trinitarianism that runs into insurmountable problems. Following Kathryn Tanner, I argue for replacing trinity with Christology as a more fruitful basis for connecting divinity and humanity. While there are many resources for a theology of polyamory in the person of Jesus, the conciliar doctrine of the incarnation provides the most fruitful ground for an ethics of noncompetitive abundance, over against mononormativity’s logic of competitive scarcity.